An Investigation Into Linguistic Features Of Education Brochures In English And Vietnamese - Phạm Thái My (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims to conduct an investigation into education brochures in English and Vietnamese. The detailed description of the typical linguistic features of education brochures are illustrated by both descriptive and contrastive method in order to point out the similarities and differences between education brochures in English and Vietnamese in terms of their lexical choice, stylistic and cohesive devices. In addition, the findings of this study are clearly presented based on a survey on 100 brochures (50 in English and 50 in Vietnamese). The study reveals that nearly all education brochures in English and Vietnamese employ the benefactive verbs, modal verbs and adjectives bring across positive impression on the learning condition and conveniences. However, the total of them used in EEBs is higher than in VEBs. According to the result of stylistic devices investigation, education brochure composers prefer using three kinds: Repetition, Parallelism and Rhetorical Questions. The frequently - used cohesive de